A study on tensor product surfaces in low-dimensional Euclidean spaces - Etemad Dehkordy, A. (Український математичний журнал, 2012)
We consider a special case for curves in two-, three-, and four-dimensional Euclidean spaces and obtain a necessary and sufficient condition for the tensor product surfaces of the planar unit circle centered at the origin and these curves to have a harmonic Gauss map. Розглянуто спецiальний випадок для кривих у дво-, три- та чотиривимiрних евклiдових просторах i отримано необхiдну та достатню умову, за якої поверхнi тензорного добутку плоского одиничного кола з центром у початку координат та цих кривих мають гармонiчне гауссове зображення.